EXPERIMENTAL PARTITIONING OF ZR, NB, AND TI BETWEEN PLATINUM GROUP METALS AND SILICATE LIQUID: IMPLICATIONS FOR THE ORIGIN OF REFRACTORY METAL NUGGETS IN CARBONACEOUS CHONDRITES - Jurewicz S.R.; Jones J.H.; Fegley B. (My University, 1995)
Reports of percent level concentrations of normally lithophile elements such as Zr, Nb, and Ta in some refractory noble metal nuggets in CAIs raise important questions about the redox state of the early solar nebula. Consequently, we have determined the metal/silicate liquid partition coefficients for Zr, Nb, and Ti at 1548 K and solar oxygen fugacity (fo2 # 10-16 bar). In most experiments, these elements formed intermetallic compounds with Pt-metal. Even though our partition coefficients for Zr (2.06-4.55) were substantially greater than previously determined values, they are still too small to account for percent levels of Zr in a refractory metal nugget from an average CAI. In addition, partition coefficient values obtained for Nb and Ti show an extremely strong affinity for the metal phase. Yet, Nb is rarely observed in refractory metal nuggets and Ti has never been observed. Given the abundance of Ti in CAIs, substantial concentrations of Ti should be present in refractory metal nuggets. This discrepancy is attributed to either: (1) the solar fo2 was too oxidizing during condensation to form the predicted intermetallic compounds; or (2) the lithophile elements originally formed intermetallic compounds with Pt-metals during condensation in the solar nebula but were subsequently oxidized in a latter heating event. Whereas our experiments suggest that conditions were never reducing enough for Ti to alloy with Pt metal, other redox determinations (e.g. Ti3+4+ ratios in CAI) imply approximately solar oxygen fugacities. Our experiments serve to emphasize the range in redox states implied by metal and silicate assemblages in CAI.